GINÁSTICA: PRODUÇÃO DE MATERIAL DIDÁTICO/PEDAGÓGICO - Göller, Dari F.; Fernandes, Raone B.; Baldissera, Lucas F. F.; Kuhn, Ohana T.; Fiedler, Felicitas; Crescêncio, Cláudio R.; Bertollo, Mauro; Filho, Leopoldo S. (Salão do Conhecimento, 2013)
Resumo